2016
DOI: 10.18632/oncotarget.11691
|View full text |Cite
|
Sign up to set email alerts
|

A directly negative interaction of miR-203 and ZEB2 modulates tumor stemness and chemotherapy resistance in nasopharyngeal carcinoma

Abstract: miR-203 is a tumor suppressor that is disregulated in numerous malignancies including nasopharyngeal carcinoma (NPC). However, the role of miR-203 in suppressing tumor stemness, chemotherapy resistance as well as its molecular mechanisms are unclear. In this study, we observed that miR-203 suppressed cell migration, invasion, tumor stemness, and chemotherapy resistance to cisplatin (DDP) in vitro and in vivo. miR-203 exerted these effects by targeting ZEB2 and downstream epithelial-mesenchymal transition (EMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
(42 reference statements)
1
32
0
Order By: Relevance
“…Jiang et al . demonstrate a direct negative feedback loop between miR‐203 and ZEB2 participating in tumor stemness and chemotherapy resistance of nasopharyngeal carcinoma . Zhang et al .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Jiang et al . demonstrate a direct negative feedback loop between miR‐203 and ZEB2 participating in tumor stemness and chemotherapy resistance of nasopharyngeal carcinoma . Zhang et al .…”
Section: Discussionmentioning
confidence: 59%
“…Jiang et al demonstrate a direct negative feedback loop between miR-203 and ZEB2 participating in tumor stemness and chemotherapy resistance of nasopharyngeal carcinoma. (25) Zhang et al report that miR-203 was epigenetically silenced, and the silencing promoted tumor cell growth and invasion at least in part by upregulating the Snai2 transcription factor in malignant breast cancer cells. (27) In this study, hepatectomy downregulated expression of E-cadherin and upregulated expression of vimentin and N-cadherin, whereas miR-203 overexpression upregulated E-cadherin expression and downregulated expressions of vimentin and Ncadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Wang, et al found that c-MYB strengthens the stemness of NPC cancer stem cell via down-regulating miR-143, thereby increasing the resistance to radiotherapy [86]. Other articles also mentioned the effects of miRNAs on the stemness of nasopharyngeal carcinoma cells and the regulation of apoptosis and damage repair of cells by affecting stemness [87].…”
Section: Mirnas Participate In Radiotherapy Resistance Of Nasopharyngmentioning
confidence: 99%
“…For instance, miR-203 has been documented to suppress NPC cell migration, invasion, tumor stemness, and chemotherapy resistance to DDP in vitro and in vivo, by targeting ZEB2 and downstream EMT and tumor stemness signals. 19 The miR-10b is upregulated in HNE1/DDP cells, and inhibition of miR-10b expression reversed the EMT phenotype. 20 Multiple molecules and various signaling pathways are involved in chemoresistance in human malignancies.…”
Section: Introductionmentioning
confidence: 98%